No one was turned away : the role of public hospitals in New York City since 1900 - Opdycke, Sandra (Oxford University Press, 1999)
No One Was Turned Away is a book about the importance of public hospitals to New York City. At a time when less and less value seems to be placed on public institutions, argues author Sandra Opdycke, it is both useful and prudent to consider what this particular set of public institutions has meant to this particular city over the last hundred years, and to ponder what its loss might mean as well. Opdycke suggests that if these public hospitals close or convert to private management - as is currently being discussed - then a vital element of the civic life of New York City will be irretrievably lost.